(untitled) (The Research of Medical Science Review, 2025)
This study, conducted at the Gastroenterology Clinic from November 2024 to March 2025, aimed to evaluate the prevalence of culture-negative neutrocytic ascites (CNNA) in cirrhotic patients with ascites. A total of 73 patients aged 30-60 years were included, with 6 months or more of cirrhosis. The study excluded patients with non-cirrhotic ascites, recent antibiotic use, or significant comorbidities. Laboratory tests and abdominal ultrasound were performed, followed by diagnostic paracentesis to analyze ascitic fluid. CNNA was diagnosed when neutrophil count was greater than 250 cells/mm³ without bacterial growth. The study found that 31.5% of patients had CNNA. Longer disease duration, low serum sodium, and low serum albumin were significantly associated with the presence of CNNA. The results emphasize the importance of considering CNNA in the diagnosis of ascites in cirrhotic patients, especially those with advanced liver disease, and highlight the need for improved diagnostic and management strategies for these patients.